Large enhancement of thermal conductivity of aluminum-reduced graphene oxide composites prepared by a single-step method. Issue 1 (9th January 2023) - Mitra, Arijit; Sahoo, Mihir Ranjan; Samal, Aiswarya; Pradhan, Sunil Kumar; Polai, Balaram; Sahoo, Krishna Rani; Kar, Subrat; Satpathy, Bijoy Kumar; Narayanan, Tharangattu N; Ajayan, Pulickel M; Satyam, Parlapalli V; Nayak, Saroj K
Abstract: Metal matrix composites have attracted extensive attention from both the research and industrial perspective. In this study, we prepared aluminum-reduced graphene oxide (Al–rGO) composites with enhanced thermal conductivity in an easy single-step process. Pristine Al shows a thermal conductivity of 175 Wm −1 K −1 (standard deviation <5%), which increases to 293 Wm −1 K −1 for an Al–rGO composite with 1% rGO. Analysis of theoretical models shows that a higher percentage of rGO inside the Al matrix creates a continuous network resulting in more available phase space through which heat carrier phonons travel with less scattering, and hence thermal conductivity of the composite increases. Furthermore, Al–rGO composites show an ∼5% increase in microhardness compared with pristine Al. The electrical resistivity of the composite is comparable to that of pristine Al for a narrow weight percentage of rGO, whereas a 70% enhancement in the thermal conductivity of the composite is observed for the same weight percentage range, suggesting possibilities for exploiting both high electrical and thermal conductivities for various applications.